Group banking : a form of banking concentration and control in the United States - Lamb, W. Ralph (New Brunswick, N.J. : Rutgers University Press, 1962)
The book takes a new look at group banking by placing it in proper perspective within the entire structure of commercial banking. The book contains the latest available data on bank holding companies, together with a treatment of recent changes in baking law and administrative procedures.
Includes bibliographical references and index.
oif 19/08/2019
Loans
Keywords: Banks and banking; Branch banks